Ethno-religious identity and the quest for community policing participation in Nigeria - Abubakar, Dalhatu Saidu; Othman, Zaheruddin; Mustaffa, Jamaludin (2017)
Community policing is an awe-inspiring mechanism for managing crime and social problems. However, ethnic and religious identity and conflicts have lean towards to affect the efficacy and viability of the community policing program in Nigeria. With a strong commitment and plans by the government in addressing crime and other social ills, through community policing, almost no outcomes appear to be imminent because Nigeria is continuously overloaded by ethnic and religious sentiments. This paper investigates the impact of ethnic and religious identity and conflict on Nigerian’s community policing program.The paper contends that ethno-religious identity and conflict not only undermines the viability and efficacy of community policing to foster security, additionally debilitates the unity and stability of the country.The fundamental argument is that unrestrained competition among the various ethnic and religious groups have affected public relations, and endanger the citizens’ participation in community policing program negatively. The paper concludes that, enlightenment campaign, especially among youth on ethno-religious tolerance, citizens’ participation in collective security, inter-religious and ethnic tolerance and harmony, police officers’ effective interaction with the citizens would restore public confidence, thereby enhances citizens’ participation in community policing program.